Cardiac resynchronization therapy for ischemic myopathy. (June 2017) - Ikeda, Shinichiro; Yoshida, Hideo; Yunoki, Keiji; Hisamochi, Kunikazu
We performed coronary artery grafting, mitral valve plasty, and tricuspid plasty in a 75-year-old man who had double-vessel coronary disease and moderate mitral and tricuspid insufficiency. Preoperative transthoracic echocardiography revealed an ejection fraction of 34% and dyssynchronous wall motion of the septum and free wall. We placed pacing leads on the right ventricular outlet and posterior left ventricular wall for cardiac resynchronization therapy. The dyssynchrony disappeared postoperatively and the New York Heart Association functional class improved from IV to I.